On Quasi Generalized Exchange Algebras (European Journal of Pure and Applied Mathematics, 2024)
A new type of algebraic structure, called a quasi generalized exchange algebra(qGE-algebra), with the GE-algebra conditions  is introduced and  its properties are investigated. The concepts of qGE-subalgebra, qGE-filter, closed qGE-filter and strong qGE-filter of a quasi GE-algebra are introduced and their relationships are discussed. The conditions for a subset of a quasi GE-algebra to be a qGE-filter  are given.
Keywords: quasi GE-algebra; qGE-subalgebra; qGE-filter